FRI0609 Usefulness of FDG-PET/CT imaging and serological biomarkers to predict relapse in IGG4-related disease. (15th June 2017) - Kato, M; Ozaki, H; Kameda, T; Izumikawa, M; Nakashima, S; Shimada, H; Wakiya, R; Kondo, A; Kadowaki, N; Dobashi, H
Abstract : Background: IgG4-RD shows relapses frequently. It is important to search to the factors to predict relapse. Recent research has shown the usefulness of FDG-PET/CT for IgG4-RD because it is more sensitive than conventional imaging to detect organ involvement of the disease. It has been suggested that FDG-PET/CT is also useful for monitoring therapeutic response of IgG4-RD. Objectives: We investigate the usefulness of FDG-PET/CT imaging and serological biomarkers to predict relapse in IgG4-RD. Methods: We analyzed 24 patients with IgG4-RD treated for more than 1 year between 2008 and 2016 in our facility. The diagnosis for IgG4-RD was based on comprehensive diagnostic criteria for IgG4-RD. All cases underwent FDG-PET/CT at least once, and laboratory data were collected from their medical records retrospectively. Levels of serum C-reactive protein (CRP), eosinophil/leukocyte ratio, serum IgG, IgG4, IgA, IgM, IgE, sIL2-R and serum compliment were investigated. Results: The patients had a mean age of 67.9 years (range: 50–87 years). In the cases with high FDG uptake on FDG-PET/CT, they had a greater number of organ involvements, higher serum IgG and sIL-2R levels. Eight patients experienced relapses following treatment. Higher serum IgG predicted relapses of IgG4-RD. FDG-PET/CT findings at baseline were not associated with relapse. FDG-PET/CT was performed in 13 patients after initiation of treatment and 4 patients had a relapse. There were no significant reduction of abnormal FDG uptake in 6 patients, and 4 of 6 patients relapsed. Conclusions: In this study, we examined the factors to predict relapse in IgG4-RD. Patients with higher serum IgG were regarded as a risk of relapse, but FDG-PET/CT findings at baseline were not associated with relapse. FDG-PET/CT reexamined after initiation of treatment is useful to predict relapse of IgG4-RD. References: Umehara H, Okazaki K, Masaki Y, et al. Comprehensive diagnostic criteria for IgG4-related disease (IgG4-RD), 2011. Mod Rheumatol. 2012 Feb;22(1):21–30. Nakatani K. Utility of FDG PET/CT in IgG4-related systemic disease Clin Radiol. 2012 Apr;67(4):297–305. Zhang J, Chen H, Ma Y, et al. Characterizing IgG4-related disease with 18F-FDG PET/CT: a prospective cohort study. Eur J. Nucl Med Mol Imaging. 2014;41:1624–1634. Disclosure of Interest: None declared